Dinamika “Timur” dan “Barat” dalam Tokoh Boonyi Kaul Noman dalam Shalimar The ClownKarya Salman Rushdie - Arumsari, Chysanti (Paradigma: Jurnal Kajian Budaya, 2011)
As the concepts of “West” and “East are not only recognized in area studies, they are also known in the study of culture. Both concepts represent a culture, of which they are not always in agreement, but are often opposition, one against another. Shalimar the Clown, a novel by Salman Rushdie presents “West” and “East” using India for its main background. The research analysizes Boonyi Kaul Noman, one of the main characters, who shook the dichotomi of West against East within the paradigms of Orientalism and Occidentalism. The discussion on the construction of East defines the relationship between the locality and role of Boonyi in the family and in the society. At the same time, the construction of “West” covers the analysis of opinion, life and role of the main character. The cultural approach and Edward Said’s theory on Orientalism-Occidentalism (1978) are applied to analize and break the dynamic of the concepts of “East” and “West.”